K.H. Hasyim Asy’ari: The Reformer of Islamic Education of East Java - Muspawi, Mohamad (Jurnal Pendidikan Islam, 2018)
K.H. Hasyim Asy’ari gait on Islamic education in Indonesia is the real act of governance developing power. The Thought and the Islamic Education dakwah K.H. Hasyim Asy'ari give good benefits to Muslim Indonesia. Pondok Pesantren Tebuireng Jombang East Java is the historical evidence concerning to development of Islamic education in Indonesia. This article aims to examine the contribution of K.H. Hasyim Asy’ari on the development of Indonesia Islamic Education. This research uses a qualitative method with literary research. The paper presents a scientific issue on the contribution of K.H. Hasyim Asy'ari Thoughts for Indonesia Islamic Education. First, the developing Education takes by Pondok pesantren Tebuireng Jombang. Second, improving Education goes from Nahdlatul Ulama (NU) organization. Third, witting education makes the development of Kitab Kuning. The three points will be discussed in this paper.